Management of Agricultural Waste as an Alternative Energy Source and Value-Added Product - Indriyani, Indriyani; Sutrisno, Eko (West Science Agro, 2025)
The increasing volume of agricultural waste in Indonesia presents both environmental challenges and opportunities for economic development. This study explores the management of agricultural waste as an alternative energy source and as a basis for value-added products through a qualitative approach. Data were collected from five key informants, including farmers, entrepreneurs, and government officers involved in agricultural waste management. The findings reveal that agricultural waste can be effectively converted into bioenergy, organic fertilizers, animal feed, and eco-friendly products, contributing to environmental sustainability and local economic growth. Challenges identified include limited technical knowledge, inadequate infrastructure, regulatory gaps, and market access constraints. The study highlights the importance of technology adoption, stakeholder collaboration, and supportive policies to optimize agricultural waste utilization in Indonesia.